The Use of Education Game Media with Animated Videos to Improve Vocabulary Mastery of Secondary School in Thailand - Henny Sembiring; Mandra Saragih (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
Vocabulary mastery is a fundamental component of English language learning, particularly in EFL contexts where students have limited exposure to English outside the classroom. However, many secondary school students in Thailand still experience difficulties in acquiring basic English vocabulary, which affects their comprehension and classroom participation. This study investigates the effectiveness of education game media with animated videos in improving students’ English vocabulary mastery. The study employed a quantitative approach using a one-group pre-test and post-test quasi-experimental design. The participants were 15 secondary school students from one class in a Thai secondary school. Data were collected through vocabulary tests administered before and after the implementation of animated video-based instruction integrated with game activities. The instructional treatment was conducted over four meetings during regular English lessons. The data were analyzed using descriptive statistics and inferential analysis to examine differences between pre-test and post-test scores. The findings indicate that education game media with animated videos has a significant positive effect on students’ vocabulary mastery. The use of animated visuals, audio input, and interactive games promotes active engagement and supports vocabulary learning more effectively than traditional instruction.